Developmental dysplasia of the hip in infants younger than six months: Ultrasonographic assessment in relation with risk factors - Al Shehri, Fahad; Almalki, Yahya (International Journal of Health Sciences, 2023)
Objectives: In newborns, developmental dysplasia of the hip (DDH) is an abnormal development of the hip joint but its accurate detection is challenging. This study was designed to determine an accurate detection of DDH and their associated risk factors in infants younger than six months using sonographic and clinical examinations. Methods: Infants younger than six months (n=404) with their hip instability were recruited. Infants’ hips were examined by ultrasonographic and clinical examinations. Ultrasonographic data were accessed in relation with the risk factors. Omni calculator was used to measure sensitivity, specificity and accuracy. Results: Out of 808 hips, 97.3% hips were categorized as Graf I type, 1.4% hips were Graf type IIa, 0.87% were type IIb and 0.49% were type IIc. The data revealed that 93.9% hips were congruous and 6.1% hips were immature. Importantly, the data showed that risk factors such as mode of delivery, breech presentation, oligohydramnios, family history and malformations were proportionally associated with positive DDH cases. Interestingly, the sensitivity, specificity and accuracy of ultrasonography in relation with clinical positivity of DDH infants were 51.83%, 99.43% and 73.16%, respectively. Conclusions: This study proved that ultrasonographic assessments are highly sensitive, specific and accurate for the detection of DDH onset in infants younger than 6 months. In addition, the study investigated a number of risk factors associated with the onset of DDH, therefore, it is extremely important that ultrasonography and clinical examination should be performed by those sonographers and orthopedic surgeons, who will have the knowledge of associated risk factors.